Di-ureasil hybrids doped with LiBF4: attractive candidates as electrolytes for "Smart Windows" - Barbosa, P. C. (2011)
The sol-gel process has been used to prepare hybrid electrolytes composed of a poly(oxyethylene) (POE)/siloxane hybrid network doped with lithium tetrafluoroborate (LiBF4) with compositions of n between ∞ and 2.5. In this context the lithium salt concentration is expressed in terms of the number of oxyethylene units in the organic component of the network per Li+ ion. Electrolyte samples with n ≥ 20 are thermally stable up to approximately 250 ºC. All the materials synthesized are semi-crystalline: in the composition range n ≥ 15 free crystalline POE exists and at 60 ≥ n ≥ 2.5 evidence of the presence of a crystalline POE/LiBF4 compound has been found. At n = 2.5 this latter crystalline phase coexists with free salt. The room temperature conductivity maximum of this electrolyte system is located at n = 10 (1.5x10-5 S cm-1 at 22 ºC). The electrochemical stability domain of the sample with n = 15 spans about 5.5 V versus Li/Li+. This new series of materials represents a promising alternative to the LiTFSI- and LiClO4-doped POE and POE/siloxane analogues. Preliminary tests performed with a prototype electrochromic device (ECD) comprising the sample with n = 8 as electrolyte and WO3 as cathodically coloring layer are extremely encouraging. The device exhibits switching time around 50 s, an optical density change of 0.13, open circuit memory of about 4 months and high coloration efficiency (106 cm2C-1 in the 3rd cycle).